Is there a common currency in asean 5? a purchasing power parity and generalized purchasing parity analysis - Rifka Ashiyamawati; Siti Aisyah Tri Rahayu (INOVASI, 2022)
The aims of this study is to examine international parity between 5 ASEAN countries to find the possibility of common currency among 5 countries in ASEAN. The interdependence of currencies in ASEAN 5 region towards Dollar creates a suggestion that the common currency should be the solution for ASEAN 5 to reach the stability of the exchange rate. The results of PPP to measure the possibility of a common currency shows that the conditions of the nominal exchange rate and price index in ASEAN 5 are cointegrated. The results of GPPP using the Johansen cointegrated test shows that there are long-term cointegrations of REER variables in ASEAN 5. Although the results of the coefficient Î² test in Johansen cointegration show that there are some unsimilar coefficient signs between the nations. So, the formation of a common currency in ASEAN 5 can not be fully realized.